(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
ريف صفوف تعقيد جديدة لحاسبة تورينك اللاحتمية بزمن P-NP-problem is the most important issue in computing theory and computational complexity,Through her study has been defined and studied the ranks of other complexity such ascoNP, PP, .. In this paper we have defined new complexity classes forpolynomial time nondeterministic Turing Machine using prime and composite numbersfor k-prime numbers and we have proven that is a subclass of it and the class is a subclass of